CD49d is a disease progression biomarker and a potential target for immunotherapy in Duchenne muscular dystrophy. Issue 1 (December 2015) - Pinto-Mariz, Fernanda; Rodrigues Carvalho, Luciana; Prufer De Queiroz Campos Araujo, Alexandra; De Mello, Wallace; Gonçalves Ribeiro, Márcia; Cunha, Maria; Cabello, Pedro; Riederer, Ingo; Negroni, Elisa; Desguerre, Isabelle; Veras, Mariana; Yada, Erica; et al.
Abstract Background Duchenne muscular dystrophy (DMD) is caused by mutations in the dystrophin gene. The immune inflammatory response also contributes to disease progression in DMD patients. In a previous study, we demonstrated higher levels of circulating CD49dhi and CD49ehi T cells in DMD patients compared to healthy control. DMD patients are clinically heterogeneous and the functional defect cannot be correlated with genotype. Therefore, it is important to be able to define reliable noninvasive biomarkers to better define the disease progression at the beginning of clinical trials. Results We studied 75 DMD patients at different stages of their disease and observed that increased percentages of circulating CD4+ CD49dhi and CD8+ CD49dhi T lymphocytes were correlated with both severity and a more rapid progression of the disease. Moreover, T+ CD49d+ cells were also found in muscular inflammatory infiltrates. Functionally, T cells from severely affected patients exhibited higher transendothelial and fibronectin-driven migratory responses and increased adhesion to myotubes, when compared to control individuals. These responses could be blocked with an anti-CD49d monoclonal antibody. Conclusion CD49d can be used as a novel biomarker to stratify DMD patients by predicting disease progression for clinical trials. Moreover, anti-CD49d peptides or antibodies can be used as a therapeutic approach to decrease inflammation-mediated tissue damage in DMD.